2014
DOI: 10.5433/1679-0359.2014v35n4p1739
|View full text |Cite
|
Sign up to set email alerts
|

Moscas-das-frutas (Diptera: Tephritidae) associadas às frutíferas nativas de Spondias spp. (Anacardiaceae) e Ximenia americana L. (Olacaceae) e seus parasitoides no Estado do Piauí, Brasil

Abstract: Moscas-das-frutas (Diptera

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
2
5
0
1
Order By: Relevance
“…Similar results were observed by Araújo et al (2014), who also recorded parasitism frequency in A. obliqua by O. bellus (78.61%) followed by D. areolatus (21.39%) in the municipality of Teresina. In other areas, the frequency of D. areolatus is higher than that of O. bellus (ALVARENGA et al, 2009;ARAUJO, ZUCCHI, 2002; and that of U. anastrephae .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were observed by Araújo et al (2014), who also recorded parasitism frequency in A. obliqua by O. bellus (78.61%) followed by D. areolatus (21.39%) in the municipality of Teresina. In other areas, the frequency of D. areolatus is higher than that of O. bellus (ALVARENGA et al, 2009;ARAUJO, ZUCCHI, 2002; and that of U. anastrephae .…”
Section: Resultssupporting
confidence: 75%
“…The preference of A. obliqua by genus Spondias, especially S. mombin, has been observed not only in the state of Piaui (ARAÚJO et al, 2014) but also in several other states, such as Rio de Janeiro (LEAL et al 2009), Minas Gerais (PIROVANI et al, 2010, Bahia (BITTENCOURT et al, 2012), and Amapa (DE DEUS, ADAIME, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al (2012) registered a quarterly viability, from August to October, 2010, of 59.60% of pupal viability in organic guava in Maceió, (AL), a very similar value to the one hereof in September and also under northeastern semiarid conditions. On the other hand, the pupal viability was similar to the one hereof, with 52.5% of the fruits obtained from three cities of Piauí (Araújo et al, 2014). In Bahia, the pupae viability was of 71.2% in cajá orchard (Silva et al, 2008) because, in Spondias, flies usually present a good development.…”
Section: Monthsupporting
confidence: 74%
“…However, based on geometric morphometry and molecular analyses, it was concluded that specimens with yellowish tibiae actually belong to O. bellus as well (Marinho et al 2014). Opius bellus is quite common in several fruit-fly surveys, recorded in 22 Brazilian states, and is predominant in the state Amazonas (Canal et al 1994(Canal et al , 1995 and Piauí (Araújo et al 2014, Vilanova et al 2016, Souza et al 2017. It parasitizes 19 species of Anastrepha, including some of economic importance, and C. capitata (see Zucchi & Moraes 2008;2012).…”
Section: Doryctobracon Crawfordimentioning
confidence: 99%